Les études récentes sur Gramsci en Italie - Giuseppe Vacca (Laboratoire Italien)
The article offers a “wide-angle lens” view of the most recent discussions on Gramsci in Italy and shows how their publication of new documents, or new editions of already-known documents, has been intertwined with critical discussion. Albeit with many interpretative oscillations and divergences, a common aspect characterizes this discussion, which may be summed up in two points, namely method and merit. Regarding the first of these, diachrony comes to the fore as the sine qua non for understanding Gramsci’s thought at each moment of his life. On the second point – the questions of merit – we show, in agreement with the first point, how all the contributions examined, as the red thread that runs through them, take account of the fact that Gramsci was above all else a practising, active politician, and only in so far as he was such was he also a theoretician of politics. We thus succeed in grasping the originality of the personality and thought of Gramsci, and avoid falling into the types of “academic” reconstruction – very widespread up to the 1980s – which resolved this thought and this personality into the “sum” of their “sources”. Gramsci is thereby restored to the history of his party, but at the same time the fact emerges that his legacy goes beyond that tradition and belongs to the whole of Italian culture.